(untitled) (Research, Society and Development, 2020)
Chemical washing is one of the main methods of document forgery, in which a reagent is applied to remove the original records from the document and insert false information. In an attempt to curb crimes of chemical washing using active chlorine, this work aimed to develop a polymeric film based on starch, capable of revealing the place where the forger has removed the records in a document. A chlorine-sensitive reagent was added to the gel, capable of rendering the paper useless in the event of fraud attempt. Potassium iodide in contact with chlorine produces molecular iodine, forming the iodine-starch complex, which causes the appearance of stains in the place where the counterfeiter applies the washing solution. The methodology used in the work was exploratory research. Tests were carried out to determine the appropriate concentrations of the reagents, as well as the ideal consistency of the gel for an easy application and good adhesion on the paper surface. The results showed that the film adhered well on the paper and did not affect the documents security components, nor did it impair the print quality. Thus, the developed film was satisfactory in detecting attempts to wash with chlorine and can be a tool to curb crimes for documentary forgery.